2006
DOI: 10.4038/jas.v2i1.8115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and multivariate analysis in pearl millet (Pennisetum glaucum (L.) R. Br.) germplasm for dual purpose

Abstract: Genetic variability and diversity in pearl millet (Pennisetum glaucum (L.) R.Br.) was studied with 104 germplasm accessions of different origin. Analysis of variance indicated significant variances among the accessions for all the characters studied. The maximum variation was recorded for number of tillers, number of leaves, leaf length and breadth, panicle length, leaf weight, stem weight, leaf stem ratio, green fodder yield, crude protein content and grain yield indicates the possibilities of improving these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
5
11
0
Order By: Relevance
“…It has been proved that SSRs can be suitable and efficient tool for molecular characterization of many plant species including pearl millet. Similarly, clustering between genotypes of pearl millet based on molecular markers was also recorded in other studies [11,17,[44][45][46].…”
Section: Diversity Analysis and Dendrogram Constructionsupporting
confidence: 71%
“…It has been proved that SSRs can be suitable and efficient tool for molecular characterization of many plant species including pearl millet. Similarly, clustering between genotypes of pearl millet based on molecular markers was also recorded in other studies [11,17,[44][45][46].…”
Section: Diversity Analysis and Dendrogram Constructionsupporting
confidence: 71%
“…Cluster I was the largest and turned out to be an accommodative for maximum number of genotypes. Similar results were reported by Shanmuganathan et al (2006) in pearl millet, Ramakrishnan et al (2013) in guinea grass, Krishna et al (2014) in forage oat and Damor et al (2017) in forage sorghum. It consisted of 31 genotypes followed by Cluster II and cluster VI with 11 and 6 genotypes respectively.…”
Section: Resultssupporting
confidence: 82%
“…The remaining characters contributed less genetic divergence indicating narrow genetic diversity for those characters. Shanmuganathan et al, (2006) and Kumar et al, (2015) reported similar results in Pearl millet. The distribution pattern of inbred lines on canonical graph matched mostly with the clustering pattern of hierarchical cluster analysis with few exceptions.…”
Section: Resultsmentioning
confidence: 56%
“…The preliminary evaluation of breeding material to identify potent parents for hybridization programme based on phenotypic data is fast, simple and can be considered as a general approach for assessing genetic diversity among genetically diverse lines. Likewise, grouping of genetic material based on quantitative data in pearl millet was reported by Shanmuganathan et al, (2006), Vidhyadhar and Devi (2007), Govindaraj et al, (2011), Drabo et al, (2013, Sathya et al, (2013), Upadhyaya et al, (2013), Sankar et al, (2014), Chaudhary et al, (2015), and Kumar et al, (2015). The average D 2 values within (intra cluster) distance and between (inter cluster) clusters are given in table 4.…”
Section: Resultsmentioning
confidence: 81%